Increased Risk of Thyroid Dysfunction Among Patients With Rheumatoid Arthritis - Li, Qian; Wang, Bin; Mu, Kaida; Zhang, Jing; Yang, Yanping; Yao, Wei; Zhu, Jie; Zhang, Jin-an (Frontiers in Endocrinology, 2019)
Abstract Background: Thyroid dysfunction seems to be common among rheumatoid arthritis (RA) patients, but the risk of thyroid dysfunction in RA has not been well defined. Methods: We performed a case-control study of 65 RA patients and 550 matched non-RA subjects to assess the risk of thyroid dysfunction among Chinese RA patients. A systematic review and meta-analysis was also conducted to comprehensively define the relationship between RA and thyroid dysfunction. Results: The case-control study indicated that the prevalence of thyroid dysfunction was significantly higher in RA patients than controls (OR=2.89, P＜0.001). Further subgroup analyses revealed positive correlations of RA with hypothyroidism (OR=2.28, P=0.006) and hyperthyroidism (OR=8.95, P＜0.001). Multivariate logistic regression analysis revealed an independent association between RA and thyroid dysfunction (Adjusted OR=2.89, 95%CI 1.63-5.12, P＜0.001). Meta-analysis of 15 independent studies also showed an obviously increased risk of thyroid dysfunction among RA patients (RR=2.86, 95%CI 1.78-4.58, P＜0.001). Further subgroup analysis showed RA could obviously increase risk of hyperthyroidism (RR=2.73, 95%CI 1.29-5.77, P=0.043) and hypothyroidism (RR=2.02, 95%CI 1.49-2.74, P＜0.001). Conclusion: Our study provides strong evidence for the increased risk of thyroid dysfunction among RA patients. Screening of thyroid dysfunction may be recommended for RA patients.